Analisis Validasi E-Modul Berbasis Jelajah Alam Sekitar (JAS) pada Materi Keanekaragaman Hayati - Minarti Joisangadji; Chumidach Roini; Abdullrasyid Tolangara (EDUKASI, 2025)
One of the teaching materials that can be used as a reference for students is an e-module based on Environmental Exploration (JAS) integrated problem solving. E-module based on Environmental Exploration (JAS) integrated Problem Solving is a learning media that can be used to support the learning process. The Environmental Exploration (JAS)-based e-module integrated with problem-solving makes it easier for students to solve problems in biodiversity material, which is closely related to the surrounding environment. This research aims to analyze the validation of the JAS-based integrated problem-solving e-module in class X biodiversity material. Based on the content validity results calculated using a Likert scale, validity data was obtained from 7 material experts and media experts, namely biology lecturers and biology teachers. The validation test in this study used five assessment criteria, namely, very good (SB), good (B), fair (C), poor (KB), and very poor (SKB). The material expert validation instrument obtained 90 categorized as very good, and the media expert obtained 88, categorized as very good.